2021
DOI: 10.1002/adfm.202108903
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon‐Induced Pyro‐Phototronic Effect Enhancement in Self‐Powered UV–Vis Detection with a ZnO/CuO p–n Junction Device

Abstract: It is important to detect light of low power density sensitively and fast for the application of optical communication, environmental monitoring, astronomy, and national securities. However, ZnO-based photodetectors exhibit long decay time owing to the persistent photoconductivity (PPC) and are hard to detect light with low power density efficiently. Here, a practical strategy is utilized to improve the performance of ZnO-based photodetectors by coupling the pyroelectric effect of ZnO with localized surface pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…
automobile exhaust monitoring, missile tracking, fire monitoring, etc. [1][2][3][4] Generally, the performance of UV detector is strongly depended on the sensing materials, and the wide bandgap semiconductors, which include GaN, SiC, ZnO, MoS 2 , InSe, etc, [5][6][7][8][9] are the preferred candidates owing to the high selectivity for UV light. Among them, ZnO is a prior choice for fabricating UV photodetectors at room temperature owing to the high electron mobility, [10] suitable bandgap (3.37 eV), high exciton binding energy (60 meV), [11] and low-cost preparation process with low cost.
…”
mentioning
confidence: 99%
“…
automobile exhaust monitoring, missile tracking, fire monitoring, etc. [1][2][3][4] Generally, the performance of UV detector is strongly depended on the sensing materials, and the wide bandgap semiconductors, which include GaN, SiC, ZnO, MoS 2 , InSe, etc, [5][6][7][8][9] are the preferred candidates owing to the high selectivity for UV light. Among them, ZnO is a prior choice for fabricating UV photodetectors at room temperature owing to the high electron mobility, [10] suitable bandgap (3.37 eV), high exciton binding energy (60 meV), [11] and low-cost preparation process with low cost.
…”
mentioning
confidence: 99%
“…This strategy has great potential to achieve an enhancement in the device performance. 147,148 Coupling noble metals in the nanoscale and 2D TMDs can enhance the performance of sensors signicantly. Sun et al 149 demonstrated that a photodetector modied by Ag nanocubes exhibited a prominent performance at a low operating potential.…”
Section: Functional Surfacementioning
confidence: 99%
“…Therefore, ZnO/MO heterostructures have attracted increasing interest. [29][30][31] Many physical and chemical synthesis methods are used to prepare heterostructured systems, including sol-gel, hydrothermal, co-precipitation and spray pyrolysis. A. E. Ramírez et al 32 are synthesized mixed photocatalysts from transition metal oxides (TMOs), such as Cr 2 O 3 , MnO 2 , FeO, CoO, NiO, Cu 2 O, CuO, and ZnO by the sol-gel method.…”
Section: Introductionmentioning
confidence: 99%